Production of Natural Aid Coagulant for Turbidity Removal in Kaolin Suspension - Saari, Nurul Syahirunisa (Universiti Teknologi PETRONAS, 2020)
Water crisis and contamination of water become one of the biggest threats towards the sustainable development of the society where there was lack of clean drinking water since the increased demand of pure clean water. Agricultural activities were the main contributors to water pollution and resulted in high turbidity to nearby river. Hence, the effective water treatment was required which is coagulation and flocculation process, however the usage of conventional chemical coagulant can generate an impact towards human health because of the high volume of sludge residual which it is categorized as schedule waste. This study aims to produce the natural coagulant aid from common fig, characterise the physiochemical properties in natural coagulant and evaluate the turbidity reduction in water treatment. The water extraction of the biopolymer from common fig and the jar test was conducted by adding Fe3+ concentration as coagulant for rapid mixing and biopolymer concentration as aid coagulant for the coagulation and flocculation process.